Analysis Of Patient Satisfaction Levels At Inpatient Installations At Bhayangkara Hospital Kupang - Napitupulu, Melissa Putri M.; Littik, Serlie K. A; Trisno, Idawati; Roga, Anderias Umbu; Muntasir, Muntasir (UNIVERSITAS PAKUAN, 2022)
Patients will feel satisfied if expectations equal or exceed the reality of hospital services. Reports of patient complaints at the inpatient installation at Bhayangkara Kupang Hospital show low patient satisfaction. This study aimed to determine patient satisfaction in terms of the five dimensions of quality. This research is a quantitative study with a cross-sectional design in which proportional sampling (PPS) uses For this reason, the inpatient installation at Bhayangkara Kupang Hospital requires improvement in the cleanliness of bathrooms and inpatient rooms, the comfort of the waiting room, waiting time for inpatients, the time to visit patients, and the provision of suggestion boxes.